Association between maternal mental health and early childhood development, nutrition, and common childhood illnesses in Khwisero subcounty, Kenya - Amanuel Abajobir; Daniel Maina; Elizabeth Wambui; Estelle M. Sidze (PLoS ONE, 2025)
Background Despite the significant public health burden of maternal mental health disorders in sub-Saharan Africa (SSA), limited data are available on their effects on early childhood development (ECD), nutritional status, and child health in the region. Aims This study investigated the association between maternal mental health and ECD, nutritional status, and common childhood illnesses, while controlling for biological, social, financial, and health-related factors and/or confounders. Method As part of the Innovative Partnership for Universal and Sustainable Healthcare (i-PUSH) program evaluation study, initiated in November 2019, a cohort of low-income rural families, including pregnant women or women of childbearing age with children under five, was recruited for this study. A total of 24 villages were randomly selected from a list of villages near two health facilities. Following a census to identify eligible households, 10 households per village were randomly selected. Data collection included maternal mental health, assessed using Centre for Epidemiological Studies Depression (CES-D) scale, ECD, nutritional status (anthropometric measurements), and common childhood illnesses, their symptoms, and healthcare utilization. This study presents a cross-sectional analysis of the data drawn from endline survey of 299 target mothers and 315 children. Results The majority of the mothers were aged between 25 and 34 years. The mean age of children was 3.2 years, with 53% being male. The overall maternal mental health score, as measured by the CES-D scale, was 28. Children of mothers with higher CES-D scores exhibited poorer ECD domains, lower nutritional status indicators, and increased incidence of ill-health in the previous two weeks, in both unadjusted and adjusted analyses. Individual, parental, and household factors—including maternal age, household wealth index, and decision-making regarding child healthcare—were significantly associated with children’s development, nutrition status, and health outcomes. Conclusion Children of mothers with low mental health scores demonstrated suboptimal developmental outcomes, nutritional status, and overall well-being, particularly for those from impoverished households. These findings suggest that improving the socioeconomic conditions of low-income households is essential for promoting children’s development, nutritional status, and well-being. Longitudinal studies are needed to further investigate the impact of maternal mental health on child development, nutrition, and health outcomes, considering additional factors across the maternal, newborn, and child health continuum. Trial registration for the parent and nested study ClinicalTrials.gov (NCT04068571), AEA Registry (AEARCTR-0006089) and PACTR (PACTR202204635504887).